Preoperative Anxiolytic and Sedative Effects of Intranasal Remimazolam and Dexmedetomidine: A Randomized Controlled Clinical Study in Children Undergoing General Surgeries - Cai YH; Wang CY; Fang YB; Ma HY; Gao YQ; Wang Z; Wu J; Lin H; Liu HC (Dove Medical Press, 2024)
Yu-Hang Cai,1,* Cheng-Yu Wang,1,* Yu-Bo Fang,1 Hong-Yu Ma,1 Yu-Qing Gao,1 Zhen Wang,2 Junzheng Wu,3 Han Lin,1 Hua-Cheng Liu1 1Department of Anesthesiology and Perioperative Medicine, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University; Key Laboratory of Pediatric Anesthesiology, Ministry of Education, Wenzhou Medical University; Key Laboratory of Anesthesiology of Zhejiang Province, Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of China; 2Laboratory Medicine Center, Allergy Center, Department of Transfusion Medicine, Zhejiang Provincial People's Hospital, Affiliated People's Hospital, Hangzhou Medical College, Hangzhou, Zhejiang, People's Republic of China; 3Department of Anesthesiology, Cincinnati Children's Hospital, Cincinnati, OH, 45229, USA*These authors contributed equally to this workCorrespondence: Hua-Cheng Liu; Han Lin, Department of Anesthesiology and Perioperative Medicine, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, 109 West Xueyuan Road, Wenzhou, 325000, People's Republic of China, Tel +86-13957770577, Fax +86-577-88002925, Email huachengliu@163.com; nanlinhannansh@qq.comPurpose: Remimazolam, an ultra-short-acting and fast-metabolized sedative, has only been sporadically investigated in children. This study was performed to determine the beneficial effects of intranasal remimazolam or dexmedetomidine on preoperative anxiety in children undergoing general surgeries.Patients and Methods: Ninety children were randomly and equally assigned to Group R (intranasal remimazolam 1.5mg kg− 1), Group D (intranasal dexmedetomidine 2 mcg kg− 1), and Group C (intranasal distilled water). The primary outcomes were the preoperative anxiety scores using the modified Yale preoperative anxiety scale (m-Ypas). The secondary outcomes included the cooperation behaviour of intranasal drug application, preoperative sedation levels, parental separation anxiety scores (PSAS), and mask acceptance scores (MAS).Results: Group R showed a significant low anxiety at 10 min after intranasal premedication (vs group C, P=0.010; vs group D, P = 0.002) and at anaesthesia induction (vs group C, P = 0.004). Group D showed a significantly low anxiety score only prior to anaesthesia induction (vs group C, P = 0.005). Most children in group R achieved mild sedation at 10 min (vs group C, P < 0.001; vs group D, P < 0.001), with a few progressing to deep sedation afterwards, while group D tended toward deep sedation. Compared to Group C, patients in Group R performed significantly better on the MAS (P = 0.014) and PSAS (P = 0.008). However, remimazolam did cause poor cooperation behavior to the intranasal application due to its mucosal irritation (vs group C, P = 0.001; vs group D, P = 0.010).Conclusion: Both intranasal remimazolam and dexmedetomidine can effectively alleviate preoperative anxiety in children. While intranasal remimazolam has a rapid onset, it produces only mild sedation and causes substantial nasal irritation.Trial Registration: NCT 04720963, January 22, 2021, ClinicalTrials.Gov.Keywords: dexmedetomidine, paediatrics, preoperative anxiety, premedication, remimazolam